Novel Human Anti-PD-L1 mAbs Inhibit Immune-Independent Tumor Cell Growth and PD-L1 Associated Intracellular Signalling - Margherita Passariello (Nature Portfolio, 2019)
Abstract The novel antibody-based immunotherapy in oncology exploits the activation of immune system mediated by immunomodulatory antibodies specific for immune checkpoints. Among them, the programmed death ligand-1 (PD-L1) is of particular interest as it is expressed not only on T-cells, but also on other immune cells and on a large variety of cancer cells, such as breast cancer cells, considering its high expression in both ErbB2-positive and Triple Negative Breast Cancers. We demonstrate here that PD-L1_1, a novel anti-PD-L1 T -cell stimulating antibody, inhibits PD-L1-tumor cell growth also by affecting the intracellular MAPK pathway and by activating caspase 3. Similar in vitro results were obtained for the first time here also with the clinically validated anti-PD-L1 mAb Atezolizumab and in vivo with another validated anti-mouse anti-PD-L1 mAb. Moreover, we found that two high affinity variants of PD-L1_1 inhibited tumor cell viability more efficiently than the parental PD-L1_1 by affecting the same MAPK pathways with a more potent effect. Altogether, these results shed light on the role of PD-L1 in cancer cells and suggest that PD-L1_1 and its high affinity variants could become powerful antitumor weapons to be used alone or in combination with other drugs such as the anti-ErbB2 cAb already successfully tested in in vitro combinatorial treatments.